The greatest you : face reality, release negativity, and live your purpose - Shelton, Trent; Aronica, Lou (Nelson Books, an imprint of Thomas Nelson, 2019)
Trent Shelton seemed to have it all together--until everything fell apart. A college football standout, his NFL dreams died when he was cut from multiple teams. With no job and no prospects, learning he had a child on the way and numbing himself with whatever he could find, Trent then found out one of his closest friends had killed himself. Life seemed without hope--until Trent discovered the secret to finding promise in the darkest of times. And now he shares that secret with you. Writing from deep, been-there experience, Trent walks you on a journey to become the best hope-filled version of yourself. In The Greatest You, Trent takes you through the necessary steps to become everything you are meant to be, from facing the reality of your circumstances and realizing your purpose in life, to breaking free from toxic environments and forgiving those--including yourself--who've harmed you, to learning how to guard yourself against the pitfalls of life.